Maximum Efficiency Conditions Satisfying Power Regulation Constraints in Multiple-Receivers Wireless Power Transfer - Won Lee; Woochan Lee; Dukju Ahn (Energies, 2022)
We propose the conditions for maximum overall efficiency at the constraint of satisfying asymmetric load power requirements for each receiver, for multiple-receivers wireless power transfer. Previously, the limitation of multiple-receiver analysis was that only the efficiency was maximized, whereas the requirements of load power were neglected. In many cases, conventional efficiency maximization assigns insufficient power to receivers far from the transmitter, while supplying excessive power to receivers near the transmitter. To resolve this limitation, we maximize the efficiency at the constraints of specified load power for each receiver. The proposed closed-form equation provides an optimum TX coil current amplitude, and the optimum load resistances of each receiver, to achieve the maximum efficiency at the load power regulation.